Emociones básicas que emergen en un grupo de hombres en intercambios swinger; un estudio realizado en la ciudad de Santiago de Cali. (2021)
The present research work aims to describe the basic emotions that male subjects experience when their partner participates in swinger encounters, allowing each one to narrate their experience within this community. A study carried out in the city of Santiago de Cali; of a qualitative nature, it seeks to describe the particularity of its norms, its signifiers, thoughts and forms of interaction. In that order of ideas, this work was carried out under a phenomenological design of descriptive scope, the representation and understanding of the experience of the participants is sought, which were four men with ages ranging between 22 and 50 years. It was carried out with voluntary participation for the development of semistructured interviews that responded to three categories: emotions, sexual practices and relational dynamics; It is true that there are four types of life, four different ways of conceiving a couple relationship in which they do agree is the conception they have about swinger encounters and how they relate to feel the desire for the other; It was evidenced that in each encounter basic emotions arose that mobilized these participants to carry out these practices.